Perkembangan Ruang Terbangun Kawasan Strategis Kota Kendari sebagai Penentu Perkembangan Penduduk dan Sarana Prasarana Dasar Kawasan - Yuyun Anggraini; Rosnawintang Rosnawintang; Ulfa Matoka (Universitas Batanghari Jambi, 2021)
This study was carried out to (1) identify and analyze the build-up land development of strategic areas of Kendari (2) determine and analyze the build-up land development of strategic areas of Kendari as a determinant of population and basic infrastructure. This study employed secondary data that was processed by overlaying thematic maps method and described the determinants of the build-up development of strategic areas. The results show there were the strategic areas of Kendari which experienced quite rapid build-up development but there were the strategic areas of Kendari that did not develop rapidly enough. (1)The build-up development of the strategic areas of Kendari were divided into 3 groups. The First is the rapidly developing strategic areas including Kendari Bay and City Center Area in Mandonga, Kadia, Kambu and Poasia with an average addition of built-up land area in 2010-2014 over 50%. The Second is the medium developing strategic areas including The Terminal Area in Baruga and also The Higher Education and The Provincial Government Center Area District in Kambu with an average addition of build-up land area over 10%. The Third is the low developing strategic areas including Bungkutoko Port, Industrial and Minapolitan Area in Abeli and also The Old Town Area in Kendari and Kendari Barat with an average addition of build-up land area under 10%. (2)The build-up development of Kendari Bay and City Center Area determines the development of population and basic infrastructures in the area, while The Higher Education and The Provincial Government Center Area, Bungkutoko Port, Industrial and Minapolitan Area and The old Town area do not determine the development of population and basic infrastructures in the area.